LEARNING A PARENTAL ROLE DURING THE PROCESS OF REHABILITATION AND FAMILY INTEGRATION, WITHIN PRISON SETTINGS - Startek, Ewelina; Węc, Klaudia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Family relationships can give people a valuable sense of identity, belonging, security and responsibility. Families are important to us all, but for prisoners, they can make a huge difference to rehabilitation. They can provide emotional support and a home to go to on release. They can also provide financial assistance and help to find work. All of these things can help to reduce the risk of re-offending: Research suggests that having family ties can reduce the likelihood of re-offending by 39 percent. However, not all family relationships are positive and helpful.Not all imprisoned parents have the opportunity to learn a parenting role before they are sentenced—they may have a negative experience of being parented, themselves. Therefore, prison might offer their first opportunity to learn a parental role and to learn about parental responsibilities. These new skills may enable them to break the cycle of crime, desist from future offending, and may impact on the prevention of intergenerational crime. To ensure that the process of learning parenting skills delivers its full potential, all members of a family should be involved, with adults and children learning together.